Synergetic effect of combination of AOP's (hydrodynamic cavitation and H2O2) on the degradation of neonicotinoid class of insecticide - Raut-Jadhav, Sunita; Saharan, Virendra Kumar; Pinjari, Dipak; Sonawane, Shirish; Saini, Daulat; Pandit, Aniruddha (Journal of Hazardous Materials, 2013)
In the present work, degradation of imidacloprid (neonicotinoid class of insecticide) in aqueous solution has been systematically investigated using hydrodynamic cavitation and combination of hydrodynamic cavitation (HC) and H2O2. Initially, effect of different operating parameters such as inlet pressure to the cavitating device (5-20 bar) and operating pH (2-7.5) has been investigated. Optimization of process parameters was followed by the study of effect of combination of HC and H2O2 process on the rate of degradation of imidacloprid. Significant enhancement in the rate of degradation of imidacloprid has been observed using HC+H2O2 process which lead to a complete degradation of imidacloprid in 45 min of operation using optimal molar ratio of imidacloprid:H2O2 as 1:40. Substantial synergetic effect has been observed using HC+H2O2 process which confer the synergetic coefficient of 22.79. An attempt has been made to investigate and compare the energy efficiency and extent of mineralization of individual and combined processes applied in the present work. Identification of the byproducts formed during degradation of imidacloprid has also been done using LC-MS analysis. The present work has established a fact that hydrodynamic cavitation in combination with H2O2 can be effectively used for degradation of imidacloprid. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Advanced oxidation processes; Hydrodynamic cavitation; Imidacloprid; Synergetic coefficient; Venturi

Effect of process intensifying parameters on the hydrodynamic cavitation based degradation of commercial pesticide (methomyl) in the aqueous solution - Raut-Jadhav, Sunita; Saini, Daulat; Sonawane, Shirish; Pandit, Aniruddha (Ultrasonics Sonochemistry, 2016)
Methomyl, a carbamate pesticide, is classified as a pesticide of category-1 toxicity and hence shows harmful effects on both human and aquatic life. In the present work, the degradation of methomyl has been studied by using hydrodynamic cavitation reactor (HC) and its combination with intensifying agents such as H2O2, fenton reagent and ozone (hybrid processes). Initially, the optimization of operating parameters such pH and inlet pressure to the cavitating device (circular venturi) has been carried out for maximizing the efficacy of hydrodynamic cavitation. Further degradation study of methomyl by the application of hybrid processes was carried out at an optimal pH of 2.5 and the optimal inlet pressure of 5 bar. Significant synergetic effect has been observed in case of all the hybrid processes studied. Synergetic coefficient of 5.8, 13.41 and 47.6 has been obtained by combining hydrodynamic cavitation with H2O2, fenton process and ozone respectively. Efficacy of individual and hybrid processes has also been obtained in terms of energy efficiency and extent of mineralization. HC + Ozone process has proved to be the most effective process having highest synergetic coefficient, energy efficiency and the extent of mineralization. The study has also encompassed the identification of intermediate by-products generated during the degradation and has proposed the probable degradation pathway. It has been conclusively established that hydrodynamic cavitation in the presence of intensifying agents can effectively be used for complete degradation of methomyl. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Advanced Oxidation Processes (AOPs); Hydrodynamic cavitation; Methomyl; Synergetic coefficient; Venturi